Pengaruh Brand Awareness, Brand Perceived Quality, Brand Associations, Brand Loyalty Terhadap Keputusan Pembelian Smartphone Apple Pada Konsumen Di Kota Denpasar - Wulandari, Gek Nanda; Adisti Abiyoga Wulandari, Ni Luh (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
A buying decision can be triggered by many impulses. The most basic thing that can cause decisions to arise is promotion from the company. Many types of promotions can be done such as creating an advantage. This study uses Apple's smartphone users as the research population where the number of samples is 85 people who are determined by purposive sampling and tested using multiple regression analysis techniques. Based on the results of the study, it can be seen that Brand awareness, Brand perceived quality, Brand association and Brand loyalty have a positive and significant effect partially and simultaneously on purchasing decisions. Looking at the results of the research, it is hoped that in the future Apple smartphones will be able to convince consumers that the logo for each product is only one, which is symbolized by an Apple by means of promotion and providing logo stickers for every purchase of its products. This needs to be done so that people can easily remember and have no doubt that the logo of the Apple smartphone is indeed one for all the product variants that are issued.